Solid as steel : production planning at thyssenkrupp - Schmedders, Karl; Schulze, Markus (London : SAGE Publications Ltd, 2017)
thyssenkrupp Steel Europe, a major European steel company, operates a so-called push-pickling line (PPL) in Bochum, Germany. The PPL produces a particular type of steel strips that are sold to B2B customers, mainly in the automotive industry. In spring 2014, a senior vice president of thyssenkrupp Steels production operations and one of his production managers notice that over the span of ten years the production facility regularly did not meet its planned production volumes. They set out to determine the drivers for the deviations from planned production figures with the ultimate goal to improve the production planning process at the Bochum PPL. Students will step into the shoes of Markus Schulze a production manager at thyssenkrupp Steel as he searches for performance drivers at the Bochum PPL and analyzes recent production data to build a forecasting model for production planning.
Originally published in Schmedders, K., & Schulze, M. (2016). Solid as steel: Production planning at thyssenkrupp. 5-215-250. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Thyssen Krupp AG; Production management -- Germany -- Bochum; Forecasting; Steel industry and trade